Warum die wissenschaftliche Politikberatung so unbeliebt ist; Why scientific policy advice is so unpopular - Gisela Färber (Wirtschaftsdienst, 2022)
– The manifold special features and challenges of economic policy-advising are ultimately based on the principles of trust and mutual learning. These principles, as the basis of cooperation between science on the one hand and politics and administration on the other, can go a long way towards resolving the problem of asymmetrical information between commissioners and commissionees or commission members and institutions seeking advice. It would be desirable to have more ministerial administration employees organising the advisory services who have already become acquainted during their studies with the approaches and problems of applying economic knowledge in political decisions and in administrative implementation.
Keywords: A11; A13; A23; D83; 330; Politikberatung; Politikberatung